Two Advancement Flaps for Eyelid Margin Reconstruction of Small and Medium Defects and a Novel Design to Reduce Ocular Injury - Dai X; Ma X; Zhang D; Zhang D; Li J; Xiong Z; Wang B; Liu G (Dove Medical Press, 2023)
Xinyue Dai,1,* Xu Ma,1,* Dongxue Zhang,2 Dapeng Zhang,1 Jiajun Li,1 Zenghui Xiong,3 Bingyu Wang,1 Guofeng Liu1 1Department of Plastic Surgery, the Second Affiliated Hospital of Harbin Medical University, Harbin, People's Republic of China; 2Department of Plastic Surgery, Nanjing Maternity and Child Health Care Hospital of Nanjing Medical University, Nanjing, People's Republic of China; 3Department of Plastic Surgery, the Second Affiliated Hospital of Guangxi Medical University, Nanning, People's Republic of China*These authors contributed equally to this workCorrespondence: Guofeng Liu, Department of Plastic Surgery, the Second Affiliated Hospital of Harbin Medical University, 246 Xuefu Road, Harbin, 150001, People's Republic of China, Tel +86 15545561122, Email liuguofeng1974@163.comPurpose: The key point of eyelid margin reconstruction is to keep both the support function and aesthetic appearance. The eyelid's complex anatomical structures make eyelid margin reconstruction demanding. Eyelid margin defects are conventionally classified by their width relative to the eyelid width: small, medium, or large. In this study, we introduce a reconstruction method for small to medium defects.Patients and Methods: We conducted a single-center case series of patients from the practice of a single experienced plastic surgeon at a tertiary center. We included consecutive outpatients from 2014 to 2021. The inclusion criteria were (1) eyelid margin mass and (2) willingness to receive eyelid margin reconstruction by the reported method. The exclusion criteria were (1) eyelid margin mass involving most or all of the tarsus and (2) less than one year of follow-up. Patients were followed up face to face or online. Patients' demographics, clinical characteristics and outcomes, and satisfaction were collected. The clinical outcomes were assessed and scored by two plastic surgeons.Procedure: We reconstructed the anterior lamella with an advancement musculocutaneous flap and repaired the posterior lamella with a specially designed advancement tarsoconjunctival flap, of which a piece of tarsus was shaved and the corresponding remnant conjunctiva was bent forward to cover the tarsus edge to avoid ocular injury.Results: We included 24 patients (25 lesions). Almost all patients had eyelash discontinuity. One patient presented slight notching of the lower eyelid margin. The other patients reported no complications or recurrence. The average outcome score was 1.23± 0.69, indicating that our method was excellent. All patients were very satisfied with the surgery. The average follow-up time was 5.75 years.Conclusion: We report a reconstruction method for small to medium eyelid margin defects and a novel design for preventing ocular injury, which is an especially good option for transverse defects.Keywords: eyelid margin, reconstruction, tarsoconjunctival flap, advancement flap